Theoretical research on the spin-Hamiltonian parameters of the square-planar CuS46− clusters in Cu(II)–dithiophosphonate complexes. (19th March 2017) - Mei, Yang; Liu, Gang; Peng, Ren-Ming; Zheng, Wen-Chen
ABSTRACT: The spin-Hamiltonian parameters ( g -factors g //, g ⊥ and hyperfine structure constants A //, A ⊥ ) of the square-planar CuS 6 − 4 clusters in Cu(II)–bis [4-ethoxphenyl-O-alkyl]-dithiophosphonate complexes are computed with the high-order perturbation formulas based on the two-mechanism model. The model includes the contributions to spin-Hamiltonian parameters from the vastly-utilised crystal-field (CF) mechanism concerning the CF excited states and the generally-omitted charge-transfer (CT) mechanism due to CT excited states. The energy levels of CF and CT excited states needed in the calculation are obtained from the observed optical spectra. The calculated results are in rational accordance with the experimental values. The signs of constants A // and A ⊥ are suggested and the reasons of the very small g -shifts | ∆gi | (= | gi − ge |, where ge ≈ 2.0023 and i = // or ⊥) are discussed. Abstract :